2017
DOI: 10.1080/13607863.2017.1341468
|View full text |Cite
|
Sign up to set email alerts
|

Caring for an individual with mild cognitive impairment: a qualitative perspective of health-related quality of life from caregivers

Abstract: Findings illustrate the multiple domains of HRQOL that are affected in individuals providing care for someone with MCI. Moreover, the findings highlight the need for extending support services to MCI caregivers, a group that is typically not offered support services due to the 'less severe' nature of an MCI diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 79 publications
0
18
0
3
Order By: Relevance
“…Finally, relatives of persons with MND in both countries expressed fears of becoming a caregiver. This is not surprising, as there is a universal understanding that assuming a caregiver rolea realistic possibility for relatives of persons with MND (Carlozzi et al, 2018;Seeher et al, 2013) is a stressful experience, impacting the caregiver's quality of life and wellbeing (Cross et al, 2018;Hooper and Collins, 2019). Interestingly, in a recent quantitative study conducted among 2,609 Asian American LP, aged 18-98, around a quarter of the participants expressed similar concerns (Jang et al, 2018).…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
“…Finally, relatives of persons with MND in both countries expressed fears of becoming a caregiver. This is not surprising, as there is a universal understanding that assuming a caregiver rolea realistic possibility for relatives of persons with MND (Carlozzi et al, 2018;Seeher et al, 2013) is a stressful experience, impacting the caregiver's quality of life and wellbeing (Cross et al, 2018;Hooper and Collins, 2019). Interestingly, in a recent quantitative study conducted among 2,609 Asian American LP, aged 18-98, around a quarter of the participants expressed similar concerns (Jang et al, 2018).…”
Section: Fear Of Stigmatizationmentioning
confidence: 99%
“…Depression is frequently assessed in caregiving research, but other mental health outcomes, such as anxiety and loneliness, have not been explored as extensively. In qualitative research, focus group interviews have revealed that caregivers of those with mild cognitive impairment most frequently raise issues around social well-being (e.g., change in social roles; need for social support) when discussing "important aspects of health-related quality of life," followed in frequency by mental health concerns (e.g., anger, anxiety, and need for patience; Carlozzi et al, 2018). One study showed that coresident caregivers of individuals with dementia are less likely to seek social support (Snyder et al, 2015), but we are not aware of any longitudinal research that examines whether caregivers perceive or experience increased social support after the transition to caregiving.…”
Section: Caregiver Outcomesmentioning
confidence: 99%
“…In an aging population, cognitive impairment is a major driver of both health‐related quality of life (HRQOL) and health‐care costs. Even before the diagnosis of dementia, individuals with subjective cognitive complaints report worse quality of life; care partners of these individuals experience higher levels of anxiety and burnout . As individuals progress from subjective complaints to mild cognitive impairment to dementia, health utilization and cost increase dramatically.…”
Section: Introductionmentioning
confidence: 99%